2003
DOI: 10.1191/0269216303pm595oa
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral antibiotics in a palliative care unit: prospective analysis of current practice

Abstract: All patients receiving parenteral antibiotics in a palliative care unit were prospectively monitored over a 13-month period. Of 913 consecutive admissions, 41 patients received 43 courses of parenteral antibiotics. On 27 of 43 occasions, the use of parenteral antibiotics was considered helpful (62%), in eight cases it was considered unhelpful (19%) and in a further eight cases the outcome could not be assessed (19%). The sites of infection for which parenteral antibiotics were prescribed included urinary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 4 publications
2
56
0
10
Order By: Relevance
“…For example, one study 49 reported palliative care consultations in an acute care hospital where only 8.3% of patients had HIV disease, a second study of the benefits of symptom control by a hospital based palliative care consultant and pharmacist also had only 8% of patients with HIV, 50 and a third study of parenteral antibiotics in an inpatient palliative care unit reported 15% of patients having an underlying HIV diagnosis. 51 The potential for a selection bias in HIV palliative care evaluation was demonstrated in a study that found patients reported lower levels of pain, better insight, less anxiety, and fewer spiritual problems than in providers' assessments. 24 Patient self reports are also subject to bias because of more unwell patients being unable or unwilling to participate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study 49 reported palliative care consultations in an acute care hospital where only 8.3% of patients had HIV disease, a second study of the benefits of symptom control by a hospital based palliative care consultant and pharmacist also had only 8% of patients with HIV, 50 and a third study of parenteral antibiotics in an inpatient palliative care unit reported 15% of patients having an underlying HIV diagnosis. 51 The potential for a selection bias in HIV palliative care evaluation was demonstrated in a study that found patients reported lower levels of pain, better insight, less anxiety, and fewer spiritual problems than in providers' assessments. 24 Patient self reports are also subject to bias because of more unwell patients being unable or unwilling to participate.…”
Section: Discussionmentioning
confidence: 99%
“…For three studies, we recalculated the proportion of patients in whom symptom improvement was observed to generate measures of effect comparable to that of the other studies. [6][7][8] We calculated 95% confidence intervals for sample proportions using the exact binomial method to provide precision of estimation.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Antibiotic therapy for the management of neutropenia and non-neutropenic haematologic diseases has been widely described and is regularly updated. However, there is little information regarding the management of antibiotic therapy in palliative care patients [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As palliative care focuses on relieving and preventing suffering and improving quality of life, treatment choices should be made based on symptom improvement and control. Antibiotic treatment might be considered part of a good palliative care plan in the presence of life-threatening infections, but the decision to treat can also lead to burdens due to diagnostic tests, adverse reactions to antibiotics or the use of intravenous lines [7]. Other aspects, such as patient and family wishes, the patient's overall condition and prognosis, and the potential for symptom control, must also be considered [3,[7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation